Kestabilan Fenotip Tanaman Labu Susu (Cucurbita moschata (Duchesne) Poir “Butternut”) Hasil Budidaya di Sleman D.I Yogyakarta - Hetty Nopianasanti; Budi Setiadi Daryono (Biogenesis: Jurnal Ilmiah Biologi, 2018)
Butternut pumpkin (Cucurbita moschata 'Butternut') is a horticultural commodity with great potential to be developed as food and medicine. Nutrients and unique shape cause butternut pumpkin to be popular. To supply of butternut pumpkin, required an increase in production which has superior and stable characters. This research aims to determine the stability phenotypic characters of butternut pumpkin in Sleman, Yogyakarta using quantitative data analysis of variance (One Way ANOVA) and qualitative analysis through descriptive phenotype. Based on the results, butternut pumpkin have a uniform phenotype characters but unstable in fruit’s shape and size of plant. Butternut pumpkin plants have 3 different shapes of pear or paprika form including dumbbell shape and gooseneck (pyriform), crispy texture, pale yellow (RHS greyed grange group 65) peel of fruit, strong orange (RHS orange group 24) flesh of fruit, 3-5°brix level of sweetness, long shelf life, and short harvest age (70-90 HST). The cultivated butternut pumpkin in PIAT UGM farmland has greater productivity of 3.1±0.99 kg/plant.